MEDICAL TOURISM DEVELOPMENT PECULIARITIES IN THE WESTERN REGIONS OF UKRAINE - Hladkyi, O. V.; Kylivnyk, V. S.; Rudyi, Yu. I.; Ruda, I. V.; Marchuk, O. V. (Rehabilitation and Recreation, 2022)
The purpose of this study is to analyze the features of medical tourism development in the western regions of Ukraine. The methodological basis of this study is a general scientific dialectical method. The main research methods are: the method of monographic investigations, illustrative, descriptive, analytical and scientific synthesis. There are the most important results of the study given below. The essence of medical tourism is highlighted. The most common elements of medical tourism are revealed as well as the main reasons of medical travelling are given. The classification of most important medical tourism services producers is given. The features of medical tourism development in Ukraine are revealed. The key segments of Ukrainian medical tourism international specialization are outlined. The main problems and prospects of medical tourism development in Ukraine are highlighted. The features of medical tourism development in the western regions of Ukraine are described. The main natural, social, professional, labor, service and infrastructure resources for the development of medical tourism in Lviv, Ivano-Frankivsk, Volyn, Zakarpattia regions are presented. The directions of involvement a number of sanatoriums, medical-rehabilitation and inpatient medical and health-improving centers into medical tourism of the western Ukraine are investigated. The main models of perspective development of medical tourism the western Ukraine are revealed. The main problems of medical tourism services transformation during the state of martial law in Ukraine are identified. The conclusions of this study are to outline the areas of mandatory state incentives for the development of specialized high quality medical services well known all over the world. The legal regulation of medical activities, the development of effective marketing solutions to promote medical tourism on domestic and international markets are substantiated. The most important factors of medical tourism development in Ukraine are: increasing the level of foreign languages usage in medical services, improving of accommodation and catering services, growing of engineering and transport industries development, creating a popular and internationally well-known brand of Ukrainian medical centers.